Safety and tolerability of first-line bevacizumab in metastatic colorectal cancer - (:unkn) unknown (IMPRIMATUR PUBLICATIONS, 2012)
Purpose: To determine the clinical features of bevacizumab-associated toxicities in metastatic colorectal cancer (MCRC) patients. Methods: The medical records of 60 patients with MCRC who were treated with chemotherapy including bevacizumab in the first-line setting were retrospectively evaluated. Results: Bevacizumab was administered along with irinotecan plus 5-fluorouracil/leucovorin (5-FU/LV) to 44 patients, 5-FU/LV+oxaliplatin to 8 patients, capecitabine+oxaliplatin to 6 patients and 5-FU/LV to 2 patients. The total number of the cycles received was 381 (median 6, range 1-13). The most common bevacizumab-related toxicity was grade 1-2 bleeding (28%) followed by hypertension (17%). Grade 1-2 proteinuria was seen in 8% of the patients (no grade 3-4 proteinuria). Arterial thromboembolic events (ATE) were not observed, however 3 patients (5%) had experienced grade 3-4 venous thromboembolic events. In 3 patients (5%) grade 1-2 wound complications were seen (delayed wound healing in the place of the venous access device in 2, and wound infection in 1). In addition, gastrointestinal perforation (GIP) was seen in 3 (5%) patients. Two of the patients were treated by surgical intervention and one patient died of sepsis. Conclusion: Bevacizumab is well tolerated when combined with various chemotherapy regimens. As bevacizumab is becoming widely used in the routine oncology practice, further studies which investigate the mechanism of bevacizumab-associated toxicities are warranted to develop effective management strategies for these adverse events.
Keywords: bevacizumab; bleeding; colorectal cancer; gastrointestinal perforation; hypertension; thromboembolism; RANDOMIZED PHASE-III; FLUOROURACIL; LEUCOVORIN; THERAPY; CHEMOTHERAPY; OXALIPLATIN; COMBINATION; IRINOTECAN; MANAGEMENT; TRIAL